Nutritional intervention to explore the growth potentiality of Malnad Gidda calves - Sushma, V.; Thirumalesh, T.; Nagabhushana, V.; Shettar, Vijayakumar B; Kotresh, A.M. (Indian Journal of Animal Nutrition, 2022)
The study was carried out to know the growth potentiality of malnad gidda (MG) calves by providing different levels of nutrients by dividing nine calves into three groups of three calves each in switch over design. The  calves in T1, T2 and T3 groups were fed to support 100, 150 and 200 g gain per day respectively and total DMI (g/d) and average daily gain (g/d) in the corresponding groups were 749.62 and 152.3; 788.78 and 167.8;  871.62 and 181.3 respectively. The DMI on percent of body weight in the corresponding groups were 1.89, 2.09 and 2.27 respectively. There was no significant difference in nutrient and mineral intake between the groups. The digestibility of all the nutrients increased numerically and the retention of nitrogen increased as the weight gain increased but the difference was not significant between the groups.  The DCP and TDN of the diet in T1, T2 and T3 were 7.95 and 55.63, 8.70 and 55.40, 56.29 and 9.03 % respectively. The total cost incurred in T1, T2 and T3 was Rs; 9.08, 9.76 and 12.20 per day respectively and cost of per kg  body weight gain in corresponding groups was Rs; 59.35, 58.10 and 67.40. It was concluded that the MG calves had the potentiality of gaining only around 180g /day with an average DMI of 2.0% of body weight.